Immediate-Early and Delayed Primary Response Genes are Distinct in Function and Genomic Architecture - Tullai, John W. (2007)
The transcriptional program induced by growth factor stimulation is classically described in two stages: the rapid protein synthesis-independent induction of immediate-early genes, followed by the subsequent protein synthesis-dependent induction of secondary response genes. In the current study, we obtained a comprehensive view of this transcriptional program. As expected, we identified both rapid and delayed gene inductions. Surprisingly, however, a large fraction of genes induced with delayed kinetics did not require protein synthesis and therefore represented delayed primary rather than secondary response genes. Of 133 genes induced within 4 hours of growth factor stimulation, 49 (37%) were immediate-early genes, 58 (44%) were delayed primary response genes, and 26 (19%) were secondary response genes. Comparison of immediate-early and delayed primary response genes revealed functional and regulatory differences. Whereas many immediate-early genes encoded transcription factors, transcriptional regulators were not prevalent amongst the delayed primary response genes. The lag in induction of delayed primary response compared to immediate-early mRNAs was due to delays in both transcription initiation and subsequent stages of elongation and processing. Consistent with increased abundance of RNA polymerase II at their promoters, immediate-early genes were characterized by over-representation of transcription factor binding sites and high affinity TATA boxes. Immediate-early genes also had short primary transcripts with few exons, whereas delayed primary response genes more closely resembled other genes in the genome. These findings suggest that genomic features of immediate-early genes, in contrast to the delayed primary response genes, are selected for rapid induction, consistent with their regulatory functions.